Pengaruh Environmental Awareness, Green Trust, dan Perceived Price terhadap Green Purchase Intention Cat Litter Ramah Lingkungan pada Pemilik Kucing di Jakarta Intan Irawati - Intan Irawati; Jana Sandra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of environmental awareness, green trust, and perceived price on green purchase intention toward eco-friendly cat litter among cat owners in Jakarta, Indonesia. The increasing number of cat owners has contributed to the rising use of cat litter products, particularly bentonite litter, which is considered less environmentally friendly due to its non-biodegradable characteristics. Eco-friendly alternatives such as tofu litter and wood litter have emerged as sustainable solutions; however, their adoption remains relatively limited due to price and practicality considerations.This study employed a quantitative explanatory research design using primary data collected through questionnaires distributed to 180 respondents who own cats and use cat litter products in Jakarta. The sampling technique used was purposive sampling combined with snowball sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS).The results show that environmental awareness, green trust, and perceived price have positive and significant effects on green purchase intention toward eco-friendly cat litter. Among these variables, green trust was identified as the most dominant factor influencing consumers’ intention to purchase eco-friendly cat litter products. The findings indicate that consumers are more likely to purchase environmentally friendly cat litter when they are aware of environmental issues, trust the product’s green claims, and perceive the price as reasonable compared to the benefits offered.This study contributes to the development of green consumer behavior research in the pet care industry, particularly in the context of sustainable pet waste management in urban areas.